Ecophysiological and morphological comparison of two populations of Chlainomonas sp. (Chlorophyta) causing red snow on ice-covered lakes in the High Tatras and Austrian Alps - Procházková, Lenka; Remias, Daniel; Holzinger, Andreas; Řezanka, Tomáš; Nedbalová, Linda (European journal of phycology, 2018)
Based on analyses of multiple molecular markers (18S rDNA, ITS1, ITS2 rDNA, rbcL), an alga that causes red snow on the melting ice cover of a high-alpine lake in the High Tatras (Slovakia) was shown to be identical with Chlainomonas sp. growing in a similar habitat in the Tyrolean Alps (Austria). Both populations consisted mostly of smooth-walled quadriflagellates. They occurred in slush, and shared similar photosynthetic performances (photoinhibition above 1300 µmol photons m-2 s-1), very high levels of polyunsaturated fatty acids (PUFA, 64% and 74% respectively) and abundant astaxanthin accumulation, comparable to the red spores of Chlamydomonas nivalis (Bauer) Wille. Physiological differences between the Slovak and Austrian populations included higher levels of α-tocopherol and a 13Z-isomer of astaxanthin in the former. High accumulation of secondary pigments in the Slovak population probably reflected harsher environmental conditions, since the collection was made later in the growing season when cells were exposed to higher irradiance at the surface. Using a polyphasic approach, we compared Chlainomonas sp. with Chlamydomonas nivalis. The latter causes 'conventional' red snow, and shows high photophysiological plasticity, with high efficiency under low irradiance and no photoinhibition up to 2000 µmol photons m-2 s-1. Its PUFA content was significantly lower (50%). An annual cycle of lake-to-snow colonization by Chlainomonas sp. from slush layers deeper in the ice cover is proposed. Our results point to an ecologically highly specialized cryoflora species, whose global distribution is likely to be more widespread than previously assumed.
Keywords: High Tatras; morphology; Astaxanthin; ultrastructure; alpine lake; Chlainomonas; field sample; snow algae; photosynthesis; fatty acids